A scientometric review of structure rockburst research: current trends and future directions - Zhang, Yuanhang; Xia, Yuanyou; Huang, Jian (Frontiers in Earth Science, 2023)
Based on practical construction experience, it is observed that a significant number of rockburst-prone regions exhibit structural surfaces of varying scales that exert a controlling influence on rockburst. Therefore, it is crucial to review the progress and hotspots in research on structure rockburst from a macroscopic perspective. This paper utilized CiteSpace software to summarize the references on structure rockburst research from the Web of Science Core Collection database from 2003 to 2022. The results include keyword cooccurrence and evolution analysis, and co-citation and cluster analysis. Through the in-depth analysis of structure rockburst literature, the research progress of structure rockburst in indoor experiments, numerical simulation, and on-site micro-seismic monitoring progress, the development trend and research hotspots were evaluated, and the current structure rockburst was discussed. The shortcomings of current research on structure rockbursts are discussed, and future development directions are proposed from the perspectives of structure rockburst mechanism, prediction and prevention measures.